Anticipating correlations [ a new paradigm for risk management - Engle, R. F. [ (Robert F.)] (Econometric Institute lecture series, 2009)
Introduces an important method for estimating correlations for large systems of assets: Dynamic Conditional Correlation (DCC). This title demonstrates the role of correlations in financial decision making, and addresses the economic underpinnings and theoretical properties of correlations and their relation to other measures of dependence.